Modification of the existing maximum residue level for phenmedipham in celeriac - EFSA (European Food Safety Authority) (EFSA Journal, 2021)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant UPL Europe Ltd. submitted an application to the competent national authority in Germany (evaluating Member State, EMS) to raise the existing maximum residue level (MRL) to 0.15 mg/kg for the active substance phenmedipham in celeriac. The submitted residue trials are sufficient to derive a tentative MRL of 0.15 mg/kg, pending further investigation of nature of phenmedipham residues in root crops. For this assessment EFSA considered that the available sugar beet metabolism data can be extrapolated to celeriac on a tentative basis. The acceptability of such proposal shall be further considered by risk managers. Adequate analytical methods for enforcement are available to control the residues of phenmedipham in celeriac at the validated limit of quantification (LOQ) of 0.01 mg/kg. Since the current MRL application was submitted before the finalisation of the EU pesticides peer review of the renewal of the approval of phenmedipham, the consumer exposure assessment was performed according to the conclusions on the toxicity of phenmedipham from the first approval under Directive 91/414/EEC. Accordingly, the long‐term intake of residues of phenmedipham resulting from the existing and the intended uses does not indicate a risk to consumer health. The present assessment does not consider the data gaps identified in the context of the renewal of the approval of phenmedipham under Regulation (EC) No 1107/2009 which prevented experts to derive toxicological reference values (TRVs) for phenmedipham, to derive the risk assessment residue definition for root crops other than sugar beet and to conclude on the toxicity of relevant metabolites.